Omphalomesenteric Fistula Presenting with Meconium Discharge from the Umbilicus - Yun-Hee Lee; Ka Hyun Lee; Ji-Won Han; Su Jin Cho (The Ewha Medical Journal)
The omphalomesenteric duct is an embryologic connection between the midgut and yolk sac, which typically disappears at 5th to 7th week of gestation. Failure of the obliteration process can lead to omphalomesenteric duct remnants. We report a case of a neonate with a patent omphalomesenteric duct fistula opening to the umbilicus presenting with meconium sprouting from the umbilical stump. Segmental resection of the ileum and end to end anastomosis were conducted. The patient was discharged on the 8th postoperative day without any complications, and no abnormalities were observed at the outpatient clinic follow-up up to 5 months after surgery. Here we describe the case and a review of the literature.